1994
DOI: 10.1021/np50111a011
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structure Elucidation of New Nitrile and Mustard Oil Glycosides from Moringa oleifera and Their Effect on Blood Pressure

Abstract: Bioassay-guided analysis of an EtOH extract of Moringa oleifera leaves showing hypotensive activity led to the isolation of two nitrile glycosides, niazirin [1] and niazirinin [2], and three mustard oil glycosides, 4-[(4'-O-acetyl-alpha-L-rhamnosyloxy)benzyl]isothiocyanate [4], niaziminin A, and niaziminin B. Glycoside 2 is a new compound. Niaziminins A and B have previously been obtained from the left extract as a mixture, while compound 4 is new from this source. Structural determination was accomplished by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(136 citation statements)
references
References 11 publications
9
113
0
14
Order By: Relevance
“…In fact, another finding (Mazumder et al, 1999) has shown the LD 50 of MO crude extract is about 2.8 g/kg intraperitoneally. This plant has been used traditionally for medicinal purposes (Faizi et al, 1994) and sometimes prescribed for anemia (Siddhuraju & Becker, 2003). Therefore, the plant is safe for human consumption without any undesirable effects.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, another finding (Mazumder et al, 1999) has shown the LD 50 of MO crude extract is about 2.8 g/kg intraperitoneally. This plant has been used traditionally for medicinal purposes (Faizi et al, 1994) and sometimes prescribed for anemia (Siddhuraju & Becker, 2003). Therefore, the plant is safe for human consumption without any undesirable effects.…”
Section: Discussionmentioning
confidence: 99%
“…The stem bark has been reported to contain two alkaloids, namely moringine and moringinine (Kerharo, 1969). Vanillin,, β-sitostenone, 4-hydroxymellin and octacosanoic acid have been isolated from the stem of M. oleifera (Faizi et al, 1994a).…”
Section: Phytochemistrymentioning
confidence: 99%
“…They have also been reported to contain some flavonoid pigments such as alkaloids, kaempherol, rhamnetin, isoquercitrin and kaempferitrin (Faizi et al, 1994a;Siddhuraju and Becker, 2003).…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The flowers, roots, leaves and bark of M. oleifera have long been used by the public as nutritional supplements and foods, as well as in the manufacture of perfume, skin oil and other products (12,(14)(15)(16)(17)(18)(19). Certain parts of M. oleifera (leaf, stem and root) have been demonstrated to produce various biological activities, including antiatherosclerotic (20), immune-boosting (21), anticardiovascular disease (22), antiviral (1,(23)(24)(25), antioxidant (2,(26)(27)(28), antimicrobial (27), anti-inflammatory (29) and tumor-suppressive effects (30). Due to its long history of usage and various biological effects, M. oleifera has long been the subject of research interest.…”
Section: Introductionmentioning
confidence: 99%